Algoritma General and Test Menggunakan Metode Depth First Search Dalam Penentuan Jalur Rute Terpendek - Putri, Weni Lestari; Jarti, Nanda (LPPM STIKOM Tunas Bangsa, 2023)
General and Test is a branch of knowledge that is included in the field of artificial intelligence. Success in using the system is the basic goal of artificial intelligence itself. General and test works in solving problems and finding the best solution which is used as a reference in determining the path to find the smallest value so that you can quickly go to the place to be visited and can save time and money while traveling to the location. General and test has the concept of looking for the smallest alternative path by how to find all the path values to be visited, after being processed as a whole for each path, alternative starling values will be obtained which can be used as directions. The way the General and test method works is to combine Depth First Search with a backracking system. All solutions must be discussed in full prior to testing. The procedure for working with this method must be carried out systematically in order to get a good solution. General and test has a working principle (1). Generate possible solutions (2). Test whether the solution is correct according to the required criteria. (3). If a solution has been found then exit, but if it has not been found then the next step is to repeat the steps until you find the highest result that can be used as a reference in finding the path with the least or shortest distance. The problem in this study is the lack of information in passing the smallest path because there are many paths that must be chosen to get to the destination. The benefit of this research is to help the user in providing information on the path to be passed so as to save time and costs. Alternative results are obtained that can be used as a solution, namely the A-B-G-J-M-T line = 23+15+5+11=54 KM. This discussion can be used as a reference by traders in finding the shortest alternative so as to save travel costs and time